Invasion of mimosa pigra in Tasik Temengor Lake and riverside area, Perak, Malaysia - S.M. Rezaul Karim; Mansor M. (2013)
A weed survey was done in Tasik Temengor Lake and the connecting five rivers namely Sungai Kedah, Sungai Rokan, Sungai Gadong, Sugai Enam and Sungai Telang of the lake Perak, Malaysia covering 33 kilometer area in June 2010 to record the presence of Mimosa pigra on the bank of the lake and rivers. It was expected to have idea about the spread of this notorious weed in the study area which might indicate their impacts on the biodiversity in the riverside areas. Motor operated boat was used to move through the lake and rivers. The boat was stopped at every 0.5 kilometer distance from individual sampling spots and the presence of the weed was searched for. A GPS was used to determine the distance from one sampling spot to another. The presence of the weed was recorded and informative photographs were taken. The percentage of sampling spots where the weed was noted was calculated. It was observed that more than 68% spots were found infested with the weed. The old plants were 2 to 3 meter height bearing many matured seed pods. Under the big plants many tiny seedlings of the weed were noted. Some pods of the weed were also recorded on the surface of water, especially near the weed infested area. All the information emphasized adoption of sustainable weed management strategy to control the weed in the important hotspot of biodiversity in Malaysia.